2022
DOI: 10.1155/2022/5298892
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of Pilose Antler in Treatment of Osteoporosis Based on Network Pharmacology

Abstract: Background. The purpose of this study was to demonstrate the pharmacodynamic material basis and molecular mechanism of pilose antler (PA) in the prevention and treatment of osteoporosis (OP) by the method of network pharmacology. Methods. First, the active components of PA were screened by BATMAN-TCM database, and the component targets were obtained from the SwissTargetPrediction online tool. Moreover, the relevant target genes of OP were obtained by searching the DisGeNET database. Second, the Venn diagram wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A total of 197 genes were obtained as candidate ones in PMO, and combined with GO and KEGG enrichment analyses, PIK3CA was further identified as the core gene of the PI3K-Akt pathway for affecting PMO. Notably, PIK3CA was reported to be a pivotal protein that might regulate osteoporosis progression [ 15 ]. PIK3CA could be regulated by Jiawei Buguzhi Pills and could play a therapeutic role in PMO [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 197 genes were obtained as candidate ones in PMO, and combined with GO and KEGG enrichment analyses, PIK3CA was further identified as the core gene of the PI3K-Akt pathway for affecting PMO. Notably, PIK3CA was reported to be a pivotal protein that might regulate osteoporosis progression [ 15 ]. PIK3CA could be regulated by Jiawei Buguzhi Pills and could play a therapeutic role in PMO [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA can encode the p110α catalytic subunit of PI3K and assist the PI3K/Akt pathway to regulate important cellular functions [ 14 ]. Of note, PIK3CA was identified as a hub protein that might have an impact on the progression of osteoporosis [ 15 ]. PIK3CA/Akt/GSK3β/β-catenin signaling could be activated by icariin, thereby supporting the protection against glucocorticoid-induced osteoporosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Wen et al studies showed that TNF was one of the targets of Liuwei Dihuang pills countermining bone loss and had a high binding activity with related active ingredients, which was similar to our research results [26] . Liu et al also believed that PIK3CA was one of the vital targets of pilose antlers in the treatment of osteoporosis [27] . Studies have shown that iron ions induce the expression of trigger receptor-2 and PI3K/Akt signaling pathways in myeloid cells to promote osteoclast differentiation [28] .…”
Section: Common Name Probabilitymentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%